1987
DOI: 10.1056/nejm198702123160702
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Drug Use and the Risk of Hip Fracture

Abstract: To assess the risk of hip fracture associated with the use of four classes of psychotropic drugs, we performed a case-control study of 1021 patients with hip fractures and 5606 controls among elderly Medicaid enrollees. Persons treated with hypnotics-anxiolytics having short (less than or equal to 24 hours) elimination half-lives had no increased risk of hip fracture. By contrast, a significantly increased risk was associated with current use of hypnotics-anxiolytics having long (greater than 24 hours) elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
269
5
12

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 907 publications
(299 citation statements)
references
References 17 publications
13
269
5
12
Order By: Relevance
“…We did not find any interaction between individuals clinically at risk for OSAS, hypnotics intake, and mortality, suggesting that if hypnotics trigger or aggravate OSAS they do not impact on mortality risk. The use of BZD may also favor falls and hip fractures and thus increase the risk for disability and death especially in the elderly [41,42]. However some studies have suggested that nighttime sleep problems may also be significant risk factors for falls in the elderly, independently of hypnotic use [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any interaction between individuals clinically at risk for OSAS, hypnotics intake, and mortality, suggesting that if hypnotics trigger or aggravate OSAS they do not impact on mortality risk. The use of BZD may also favor falls and hip fractures and thus increase the risk for disability and death especially in the elderly [41,42]. However some studies have suggested that nighttime sleep problems may also be significant risk factors for falls in the elderly, independently of hypnotic use [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazepínicos têm sido associados a um aumento no risco de quedas e fraturas em diversos estudos individuais (Grisso et al, 1991;Jensen et al, 1991;Ray et al, 1987Ray et al, , 1989Ryynänen, 1993), assim como numa meta-aná-lise (Leipzig et al, 1999a).…”
Section: Discussionunclassified
“…Com isso, esses indivíduos estão mais sujeitos a apresentar tonteiras, ataxia, confusão, levando ao risco aumentado de quedas. A redução da massa muscular e da densidade óssea acarreta uma (Ray et al, 1987). Os resultados que associam o uso de bloqueadores de canal de cálcio a quedas e fraturas entre idosos são inconsistentes.…”
Section: Discussionunclassified
“…• Diazepam should not be prescribed for elderly patients, since this long-acting benzodiazepine drug exposes them to the risk of falls and hip fracture. 29 • Enoxaparin: the advantages of this lowmolecular-weight heparin over conventional treatment with heparin are questionable, 30,31 especially when considering that enoxaparin is so many times more expensive than heparin. The safety of enoxaparin has not been established for this age group.…”
Section: Drug Selectionmentioning
confidence: 99%